Pengaruh Digital Marketing, Kualitas Produk dan Harga terhadap Keputusan Pembelian : (Studi pada Pengguna Yamaha Nmax Turbo di Dealer Yamaha Mustika Motor Tangerang Selatan) - Muhammad Vickry Andrha; Ravindra Safitra Hidayat (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This research aims to test and analyze Digital Marketing, Product Quality and Price on Yamaha Mustika Motor Purchase Decisions in South Tangerang. This type of research is quantitative. The population in this study is unknown. The sample used in this research was 97 respondents, using the accidental sampling method and using the lemeshow formula. In this research, the data was analyzed using the SPSS version 22 program and Microsoft Excel 2021. The research results show that in digital marketing, product quality and price have a significant effect on purchasing decisions.